Novel Situations of Endothelial Injury in Stroke - Mechanisms of Stroke and Strategy of Drug Development: Intracranial Bleeding Associated With the Treatment of Ischemic Stroke: Thrombolytic Treatment of Ischemia-Affected Endothelial Cells With Tissue-Type Plasminogen Activator - Yasuhiro Suzuki; Nobuo Nagai; Kazuo Umemura (Elsevier, 2011)
Abstract.: Previous studies have shown that the risk of intracranial hemorrhage (ICH) associated with the treatment of ischemic stroke is mainly attributable to antithrombotic agents. On the basis of clinical trials, only tissue-type plasminogen activator (t-PA) has been approved for treating acute ischemic strokes, but delayed treatment with t-PA is associated with the risk of cerebral hemorrhagic transformation of ischemic stroke. t-PA converts plasminogen to plasmin, which participates primarily in clot lysis via fibrin degradation and, to some extent, in tissue remodeling via degradation of various extracellular matrix proteins, either directly or via activation of matrix metalloproteinases (MMPs). MMPs mediate the pathogenesis of ischemic-stroke-associated ICH by causing the disruption of vasculature. In particular, the binding of t-PA with one of its receptors leads to the activation of low-density lipoprotein receptor-related protein (LRP), which in turn results in the release of MMP-3 by endothelial cells. LRP production is reported to be upregulated in endothelial cells exposed to ischemia, and elevated LRP levels have been implicated in the increased ICH risk associated with delayed t-PA treatment. This implies that the t-PA / LRP / MMP-3 pathway may be a suitable target for developing strategies to improve the therapeutic efficacy of t-PA in acute ischemic stroke. Keywords:: tissue-type plasminogen activator, cerebral ischemia, intracranial hemorrhage, matrix metalloproteinase, low-density lipoprotein receptor-related protein, endothelial injury